Pemanfaatan dan Pola Penyelesaian Sengketa Sumber Daya Air di Kecamatan Batulayar Lombok Barat - M. Yazid Fathoni; Sahnan -; Diangsa Wagian (Fakultas Hukum Universitas Mataram, 2015)
This research tries to find out and analyze: factors which bring about dispute or conflict within the making use of water resources in the sub-district of Batulayar and also its settlement. This research discovers that the possession of water resources in Batulayar is on state hand through the public work office (agency) of west Lombok and technically executed by the doorman of the main water dam which locates in the forest area of Pusuk. In relation with its distribution, the doorman of the main water dam refers to the agreement among and the request of Pekaseh (the distributors of water). Yet, however, there is always factor bring about conflict, which finally leads to dispute. Up to now, still, the dispute of water resources in the sub-district of Batulayar can always be settled through non-litigation mechanism.